Effect of Ma Yinglong Shexiang hemorrhoids cream combined with pearl powder on the pain and complications of severe pressure ulcer patients. Issue 33 (20th August 2021) - Niu, Dongling
Abstract: Objective: The aim of this study was to investigate the effect of Ma Yinglong Shexiang Hemorrhoids Cream combined with pearl powder on pain and complications in patients with severe pressure ulcers. Methods: One hundred seventeen patients with severe pressure ulcers hospitalized and treated in our hospital (January 2019–December 2019) were divided into Ma Yinglong Musk Hemorrhoid Cream Group (MY Group), Pearl Powder Group (PP Group), and combination with Ma Yinglong Musk Hemorrhoid Cream and Pearl Powder Group (MP group), 39 patients in each group. There was no significant difference in the general data of patients in MY group, PP group, and MP group. By analyzing the differences in clinical efficacy, secondary effects, scar incidence, pain, and clinical indicators of patients in the MY group, PP group, and MP group, the effects of Mayinglong Shexiang Hemorrhoid Cream combined with pearl powder in the treatment of pain and complications in patients with severe pressure ulcers were explored. Results: After treatment, compared with the MY group and the PP group, the MP group had a higher clinical efficacy than the MY group and the PP group. Compared with MY group and PP group, the healing time, dressing change times, and dressing change time of MP group were better than MY group ( P < .05). After treatment, the VAS score and incidence of secondary effects of the MP group was significantly lower than that of the MY group and PP group ( P < .05). The incidence and area of scar formation in the MP group were lower than those in the MY group and the PP group ( P < .05). Conclusion: Compared with Ma Yinglong Musk Hemorrhoid Cream or Pearl Powder, combination of Ma Yinglong Musk Hemorrhoid Cream and Pearl Powder are more effective in treating severe pressure ulcer patients, and can significantly reduce the pain in the affected area and reduce the occurrence of complications.